Wireless localization in multipath environments - Nathan Linarto (2011)
This formal report presents a wireless localization method in multipath environment. The current global positioning system (GPS) using satellite cannot localize a mobile device (MD) inside a building well. Therefore, local / indoor localization technique is proposed to localize the MD position. However, indoor environment commonly contains many obstacles which will cause several non line of sight (NLOS) paths between the MD and reference devices (RDs), which is referred to as multipath environment. Each reference devices (RDs) are equipped with antenna-arrays to enable them to obtain both time-of-arrival (TOA) and angle-of-arrival (AOA) measurements. Line-of-sight (LOS) scenario, if available, is taken in the localization process by each RD to give better localization accuracy. To minimize the NLOS localization error, a method has been proposed to identify if there are multiple RDs which obtain LOS measurements. If not available, the method will process the NLOS measured data and localize their shared reflection points. If there are three or more reflection points shared by MD and multiple RDs, the shared reflection points are localized via DOA fusion, and then the MD is localized via AOA fusion. Simulations are designed and conducted to evaluate the proposed technique in terms of the probability of the NLOS MD localization accuracy in a noisy environment. In addition, through the simulation, the proposed method will be reviewed of its space for improvement and thus new improvement techniques are also simulated and the resulting performance is compared with the proposed method.